PENGARUH INFLASI DAN ANGKATAN KERJA PADA TINGKAT PENGANGGURAN DI INDONESIA BULAN FEBUARI PERIODE 2021-2024 - Mario Setiawan; Purwanti, Purwanti (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
In Indonesia, unemployment is a problem that greatly affects social and economic stability. Using qualitative methods, this research tries to understand how the labor force and inflation affect the unemployment rate in Indonesia between 2021 and 2024. Document analysis, official government reports and related scientific publications were used to collect data. Research findings show that inflation has an indirect impact on unemployment through economic stability and has a direct impact on people's purchasing power and production costs. On the other hand, one of the main causes of increasing unemployment is the increase in the number of the workforce which is not balanced by adequate employment growth. Based on this study, the government is advised to combine sustainable employment development with inflation control measures.